Terapeutyczne aspekty nauczania języka obcego dzieci ze specjalnymi potrzebami edukacyjnymi (na przykładzie uczniów z niepełnosprawnością intelektualną w stopniu lekkim) - Burzyńska, Małgorzata (Neofilolog, 2011)
The paper is an attempt to present an overall approach to special educa-tional needs as revealed by children with mild intellectual disability in the course of learning a foreign language. It presents the results of an action re-search study conducted among primary special school pupils. The research aimed at identifying the possible range of basic skills involved in learning a foreign language, and in addition, determining the degree to which the for-eign language stimulates the use of the mother tongue by those children. The paper also presents the limitations on the therapeutic aspects of teach-ing foreign languages to learners afflicted by intellectual disability.